Comparative Analysis of Curriculum Management Practices in Indonesia and Malaysia: A Case Study of Secondary Education Systems - Sri Utami; Sofyan Tsauri; Imron Fauzi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study presents a comparative analysis of curriculum management practices in secondary education systems in Indonesia and Malaysia. Employing a qualitative library research approach, it examines the governance structures, leadership roles, teacher readiness, and implementation dynamics in both countries. Indonesia’s Kurikulum Merdeka promotes decentralized and flexible curriculum management, enabling contextual innovation at the school level. In contrast, Malaysia’s centralized KSSM ensures policy standardization but limits local adaptability. The findings reveal key challenges, including policy-practice gaps, disparities in teacher competence, and constraints in leadership capacity. Through dialog with contemporary theories such as instructional leadership, teacher agency, and curriculum governance, this study identifies the need for strategic alignment between national policy and school-level implementation. The novelty of this research lies in its regional comparison, offering insights into how educational systems in the Global South manage curriculum reform. It contributes to the discourse on equity, decentralization, and the professionalization of educators in curriculum change.